Gerakan Petani Dalam Konteks Masyarakat Sipil Indonesia: Studi Kasus Organisasi Petani Serikat Tani Merdeka (SeTAM) - Desi Rahmawati (Jurnal Ilmu Sosial dan Ilmu Politik, 2003)
Peasant movement take different form from time to time. The recent one have been strongly manifest in their struggle to encounter state's policies. In so doing, they equipt themselves with capacity to manage their autonomy, improve their access to government institutions, and making use of public sphere. The case of SeTAM shows that the peasants ara capable of presenting as an element of civil society.